DIABETIC KETOACIDOSIS - OUR EXPERIENCES - Miolski, Jelena; Ješić, Maja; Kovačević, Smiljka; Blagojević, Jelena; Zdravković, Vera (Medicinski časopis, 2021)
Diabetic ketoacidosis is an acute complication in children with type 1 diabetes mellitus. It is defined if the sugar value is> 11 mmol / l, pH <7.3, HCO3- ≤ 15 mmol / l, with ketonemia or ketonuria. Based on serum pH and bicarbonate values it could be mild, moderate and severe. It is manifested by rapid breathing, abdominal pain, nausea, vomiting, altered state of consciousness. Early recognition of symptoms prevents the possibility of serious complications. Treatment includes fluid replacement, rehydration, insulin therapy, electrolyte replacement, glucose correction. This paper presents female patients, aged 2.5 to 15.3 years, with different symptoms. Clinical findings and laboratory test results indicated diabetic ketoacidosis. After starting herapy, they were referred to intensive care units, tertiary centers, where it was concluded that the resulting condition was newly diagnosed type 1 diabetes mellitus. Such patients require early recognition of symptoms, urgent care and treatment in intensive care units, in order to prevent possible complications.